Clinical outcomes in T‐cell large granular lymphocytic leukaemia: prognostic factors and treatment response. (9th June 2020) - Braunstein, Zachary; Mishra, Anjali; Staub, Annette; Freud, Aharon G.; Porcu, Pierluigi; Brammer, Jonathan E.
Summary: T‐cell large granular lymphocytic leukaemia (T‐LGLL) is an incurable leukaemia characterised by clonal proliferation of abnormal cytotoxic T cells that can result in severe neutropenia, transfusion‐dependent anaemia and pancytopenia requiring treatment. The most commonly used agents, methotrexate (MTX), cyclophosphamide (Cy) and cyclosporine primarily produce partial remissions (PRs), with few complete responses (CRs). We evaluated the clinical course and treatment response of 60 consecutive patients with T‐LGLL to evaluate clinical outcomes and future potential treatment directions. Impaired overall survival was noted among male patients, patients with elevated lactate dehydrogenase, and those without rheumatoid arthritis. Cy was the most efficacious second‐line agent, with a 70% overall response rate (ORR; three CR, four PR). All patients who failed frontline MTX responded to second‐line Cy. In the relapsed or Cy‐refractory setting, alemtuzumab ( n  = 4) and pentostatin ( n  = 3) had an ORR of 50% and 66%, respectively, while duvelisib induced a long‐term response in one patient. In this large, retrospective analysis, our results suggest Cy is a highly effective therapy for second‐line treatment in T‐LGLL and should be considered a strong candidate for up‐front therapy in select high‐risk patients. Prospective studies evaluating pentostatin, alemtuzumab and novel agents, such as duvelisib, are needed for patients with relapsed/refractory T‐LGLL.